Pengembangan Moocs Sukses Berbisnis di Marketplace Sebagai Peluang Bisnis Online - Rahmaddian; Stefani Made Ayu Artharini Koesanto; Gunawan Wiradharma; Mario Aditya Prasetyo; Arina Rubyasih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Marketplace is a digital platform that is familiar to use when buying and selling online. Marketplaces are crucial in enhancing the quality, marketing, and competitiveness of MSME services and products. There are so many MSMEs in the form of online stores in the marketplace. The existence of a marketplace is beneficial for business owners who are just starting their business on a particular marketplace platform. However, the existence of these online stores is considered not optimal in reaching a very broad market due to the lack of experience and knowledge to make business innovations. Therefore, a training through MOOCs is needed for MSMEs that have online stores incorporated in a marketplace. using the ADDIE Model to acquire prevalent knowledge regarding business strategies in the marketplace, xMOOCs are developed. The developed MOOCs consist of seven materials, namely (1) Basic Concepts of Marketplace, (2) Marketplace Business Models, (3) Preparation for Starting an Online Business in the Marketplace, (4) Selling in the Marketplace, (5) Strategies for Increasing Traffic in the Marketplace, (6) Managing and Developing Stores, and (7) Success Stories of Online Sellers in the Marketplace. The development of MOOCs through research obtains complete information from the design, development, to evaluation stages. These MOOCs can be used massively and effectively in providing useful knowledge for participants to increase sales in the marketplace.